Novel Magnetic Phases: Spin Solid versus Magnetic Charge Ordered State in Artificial Honeycomb Lattice of Connected Elements (Adv. Sci. 4/2018). Issue 4 (19th April 2018) - Glavic, Artur; Summers, Brock; Dahal, Ashutosh; Kline, Joseph; Van Herck, Walter; Sukhov, Alexander; Ernst, Arthur; Singh, Deepak K.
Abstract : An artificial magnetic honeycomb lattice provides a facile platform to explore a multitude of novel magnetic phases, including the realization of the spin solid order. In article number1700856, Deepak K. Singh and co‐workers use neutron reflectometry, grazing incidence neutron scattering (GISANS) measurements, and temperature‐dependent micromagnetic simulations to elucidate the development of this unique magnetic phase in a newly designed artificial honeycomb lattice of ultrasmall connected elements.